ISTINBAT HUKUM ISLAM PERSPEKTIF AZ ZAHIRI - SA, Romli (Nurani, 2014)
Abstract:  Ibn Hazm (994 M-1086 M) is a controversial moslem scholar in the field of fiqh. One of his method of istinbat in law is zahiri. It focuses the interpretation at “nash” an the basis of the meaning at text. This method is principally similar to those used by other moslem scholars in his time. The difference is that the reasons used. In short, Ibn Hazm and other moslem scholars try to understand the religious matters an the basis of zahiri method or well-know as bayani pattern.ملخصابن حزم (AD 994 AD-1086) مثير للجدل في مجال الفقهاء : أسلوب واحد لصياغة القانون هو الظاهري. أنه يركز على تفسير "النصوص" في المعنى الأساسي في النص. هذه الطريقة مشابهة خاصة لتلك المستخدمة من قبل غيره من العلماء في عصره. والفرق هو أن أسباب استخدامها. باختصار، ابن حزم وغيرهم من العلماء محاولة لفهم أمور الدين هي أساس طريقة الظاهري أو نعرف جيدا ما تفسير النمط. Kata kunci:  metode zahiri, istinbat, hukum Islam